Opinions about judo athletes' image - Zaggelidis, G.; Mavrovouniotis, F.; Argyriadou, E.; Ciucurel, M.-M. (Journal of Human Sport & Exercise, 2013)
OBJECTIVE: The present study aimed to evaluate opinions of persons who are involved with judo about judo athletes` personality. METHODS: For this purpose 132 coaches, athletes, students of Department of Physical Education and Sport Science (DEPESS) and students of military school answered to a 35-item questionnaire describing their image towards judo athletes, in regard to social, volition, active, physical and emotional nature. RESULTS: statistical analysis showed that all the groups rated from the average, to somewhat strong and, also, to strong, while coaches rated higher to the most items. More specifically, one way ANOVA revealed significant differences, with coaches rating significantly higher, in the items of "being healthy" in physical nature (F=2.85, p<0.05), in items "having proper manner" and "being sincere" in social nature, (F=3.41, p<0.05 and F=3.09, p<0.05 respectively), "being positive" in active nature (F=3.95, p<0.05). Also in the items "being mild" (F=3.04, p<0.05), "being cheerful" (F=3.60, p<0.05) and "being carefree" (F=2.98, p<0.05) in emotional nature. Moreover, students of military school rating significantly higher in the item of "being cautious" in active nature (F=2.51, p<0.05) and in the item of "having power of concentration" in active nature both students of military school and of DEPESS rating significantly higher (F=5.66, p<0.01). CONCLUSIONS: The high rating in the most items might be due to the nature of the attitudes provided and cultured during the judo lessons, practice time and matches. Moreover, the differences between the groups for the coaches group might be observed because they have the most real image for judo athletes.